2023
DOI: 10.1177/10384162221140338
|View full text |Cite
|
Sign up to set email alerts
|

The impact of future work self on perceived employability and career distress

Abstract: Future work self is a promising concept to understand how young people view and plan their careers in the contemporary workplace. In this study, we attempt to investigate its impacts on two career-related outcomes, namely, perceived employability and career distress. Informed by social cognitive career theory, we also explore the mediating role of career decision self-efficacy in the above relationships. Several hypotheses were developed and tested with a sample of 208 final-year undergraduate students (with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
(118 reference statements)
0
1
0
Order By: Relevance
“…Scholars have also suggested that the perception of employability is influenced by self-concept [ 34 ]. In other words, students’ personal traits play a significant role in predicting their future employability perception [ 35 ]. When students become job seekers, they begin to focus more on their future career direction than before and are concerned about their future employability [ 36 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Scholars have also suggested that the perception of employability is influenced by self-concept [ 34 ]. In other words, students’ personal traits play a significant role in predicting their future employability perception [ 35 ]. When students become job seekers, they begin to focus more on their future career direction than before and are concerned about their future employability [ 36 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%